Notes from the youth mental health field: Using movement towards goals as a potential indicator of service change and quality improvement. Issue 3 (11th June 2021) - Jacob, Jenna; Edbrooke‐Childs, Julian; Costa da Silva, Luís; Law, Duncan
Abstract: The aim of this paper is to report our notes from the field on using movement toward goals at an aggregate level as an inference of service effectiveness. Analysis of routinely collected data from UK youth mental health services was conducted ( N = 8, 172, age M = 13.8, 67% female, 32% male) to explore the impact of including goal‐based outcome data in combined calculations of standardized measures based on the principles of reliable change ("measurable change"). Due to the broad nature of standardized measures, inferred validity becomes diluted in any team or service level aggregate analysis. To make inferences that are closer to the person's interpretation of their difficulties, we argue that Idiographic Patient Reported Outcome Measures (I‐PROMs) counterbalance these limitations. This is supported by our findings. The measurable change metric is the first step towards enabling national analysis of aggregated I‐PROMs. I‐PROMs, supplemented by standardized measures should be used to consider service evaluation.